Hakikat Iqab Dan Hukuman Dalam Pendidikan Islam - Umar, Ahmad (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2023)
Education is a maturing process of learning a very complex learners systematically through a curriculum that is applied in the educational unit that is useful to explore the potential of students from various facets of the life of society, nation and state. To realize these goals much needed discipline and sense of responsibility in the learning process. Consistency discipline and sense of responsibility in the learning process, then the required method or preventive measures, one such method is the provision of a penalty or punishment in educational units aimed accompany the learning process in order to achieve educational goals that had been expected. We need to know the substance rather than reward and punishment will not be separated in the educational process as well as the essence of good and bad are both always go hand in hand at the wheel of life. Therefore, punishment in the educational process must be in accordance with Islamic education that directs learners to always berakhlakul karimah able to distinguish between good and bad behavior in daily life both in the school environment and society in general. Purpose of punishment in Education Islam is nothing but providing guidance and improvement. Therefore, it is necessary to pay attention to the character and condition of students before a teacher gives punishment to them. By understanding the meaning of inner punishment Islamic education is based on the Qur'an and hadith, it is hoped that punishment can give positive meaning to learners.